2014
DOI: 10.3233/jvr-140710
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and cultural factors that promote creative best practices in the public rehabilitation program: Findings from a four-state multiple case study

Abstract: The state-federal vocational rehabilitation system is tasked to demonstrate accountability for employment outcomes of persons with disabilities. State VR agencies have sought to evaluate existing practices, and in areas that existing practices leave room for improvement, create the conditions for innovation to occur. The purpose of this article is to identify promising organizational and cultural factors that appear to promote best practices in the public vocational rehabilitation program. A multi-stage study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…It is also worth noting that there are numerous stalwart, rehabilitation counseling professionals who do not hold advancement aspirations, but who continue to contribute substantially to agency outcomes, the work milieu, and leadership at the direct service level. Each individual can influence the general culture through motivating others, fostering learning, encouraging innovation, and promoting agency synergy (Sherman et al, 2014). In addition, those senior counselors are often relied upon for peer consultation and guidance, as they may be more approachable or accessible during supervisory shortages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also worth noting that there are numerous stalwart, rehabilitation counseling professionals who do not hold advancement aspirations, but who continue to contribute substantially to agency outcomes, the work milieu, and leadership at the direct service level. Each individual can influence the general culture through motivating others, fostering learning, encouraging innovation, and promoting agency synergy (Sherman et al, 2014). In addition, those senior counselors are often relied upon for peer consultation and guidance, as they may be more approachable or accessible during supervisory shortages.…”
Section: Discussionmentioning
confidence: 99%
“…Sherman et al (2014) suggested the leader impacts the agency through his or her effect on the organizational culture and that agencies should consider changing from a hierarchical culture to a less structured “culture of adhocracy” which facilitates innovation by allowing greater flexibility, risk taking, and collaboration among employees. In this kind of system, decision making is decentralized, freeing up space for expressing ideas and testing innovative interventions that may be suppressed in formal hierarchies (Sherman et al, 2014). In the leadership context, this is a movement from a more transactional leadership approach to a more transformational approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that counselors cannot take on the challenge of implementing EBP on their own, and leadership will set the stage on how EBP will be (or will not be) implemented in practice. Sherman et al (2014) investigated the promising leadership and organizational factors shared by four high-performing VR agencies, and found that leaders who foster a culture of adhocracy (organizational culture that emphasizes flexibility, adaptability, and change) lead to innovative practices, including EBP. In this culture, the specific concerns of implementation of EBP by rehabilitation counselors are heard, and solutions are generated by the rehabilitation counselors utilizing the practice (Sherman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Leaders are directors on one hand, who fulfil a coordinating function, and producers on the other hand, focusing on productivity. (Denison & Spreitzer, 1991;OCAI online, 2012;Sherman et al, 2014) A more recent development is the innovation-oriented adhocratic culture, which has taken a definite shape over the past decades. This type of culture usually develops in organic and open systems or at matrix organizations.…”
Section: Organizational Culturementioning
confidence: 99%